Kajian Hukum Perbandingan Kemudahan Investasi Asing di Singapura dan di Kota Batam, Indonesia Beserta Legal Standing OSS Dalam Penerapannya - Abdurrakhman Alhakim; Jessica Sim; Hari Sutra Disemadi (Universitas Batanghari Jambi, 2021)
Investment is one of the first steps in moving the wheels of a country's economy. In the city of Batam itself is strongly identified with the investment climate. With its strategic location, Batam City is located adjacent to its neighboring countries, namely Singapore and Malaysia. The OSS (Online Single Submission) system emerged as one of the steps aimed at increasing the competitiveness of the global region and encouraging investment growth. However, in the OSS system there are still many obstacles both in terms of regulations and implementers of regulations that are considered less than optimal in applying electronically integrated business licenses. This is also worsen by the dualism of authority in managing the region. Looking to neighboring countries, Singapore is a favorite destination for global companies wishing to expand their business in Asia. The ease of obtaining a business license has become the main focus for this Lion Country. This study uses a normative legal research method with a comparative law approach and a statutory regulation approach. The purpose of writing this article is to study the ease of foreign investment in Singapore compared to Batam City and the legal standing of OSS in its application. Based on the research conducted, the ease of investment is examined from various factors, namely in the areas of legal certainty, taxation, employment, and licensing of the Indonesian OSS system including Batam City which still does not fully support a conducive investment climate in doing business compared to Singapore.